2020
DOI: 10.1186/s12862-019-1551-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring molecular evolution of Rubisco in C3 and CAM Orchidaceae and Bromeliaceae

Abstract: Background: The CO 2-concentrating mechanism associated to Crassulacean acid metabolism (CAM) alters the catalytic context for Rubisco by increasing CO 2 availability and provides an advantage in particular ecological conditions. We hypothesized about the existence of molecular changes linked to these particular adaptations in CAM Rubisco. We investigated molecular evolution of the Rubisco large (L-) subunit in 78 orchids and 144 bromeliads with C 3 and CAM photosynthetic pathways. The sequence analyses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Hermida-Carrera et al . 26 found similar results when comparing rubisco catalytic traits of orchids and bromeliads with and without CCMs. These results suggest that equipping C 3 crops with CCMs could be another strategy for fueling their photosynthetic capacity.…”
Section: Rubisco Kinetics and Co 2 -Concentrating supporting
confidence: 63%
“…Hermida-Carrera et al . 26 found similar results when comparing rubisco catalytic traits of orchids and bromeliads with and without CCMs. These results suggest that equipping C 3 crops with CCMs could be another strategy for fueling their photosynthetic capacity.…”
Section: Rubisco Kinetics and Co 2 -Concentrating supporting
confidence: 63%
“…Positive selection for rbcL is widespread among land plants ( Kapralov & Filatov, 2007 ; Yao et al, 2019 ; Shen et al, 2020 ) and several studies have demonstrated that positive selection on specific amino-acids in rubisco is linked to plant adaptation to different environmental stresses, facilitating adaptive radiation into diverse ecological niches ( Hermida-Carrera et al, 2017 ). Examples include adaptations to dry or wet climates ( Kapralov & Filatov, 2006 ; Galmés et al, 2014 ), to high altitude environments ( Hu et al, 2015 ) and in transitions from C 3 to C 4 photosynthesis ( Christin et al, 2008 ; Kapralov, Smith & Filatov, 2012 ; Hermida-Carrera et al, 2020 ), including in Flaveria (Asteraceae, tribe Tageteae) ( Kapralov et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The T. purpurea accession grouped together with one T. marconae and all T. landbeckii accessions might have captured its plastome via reticulate evolutionary processes. The second T. marconae accession (HEID103591/ Rauh20899) has been analyzed earlier in a broader context of the evolution of CAM metabolism in Bromeliaceae (Hermida-Carrera et al 2020). For this taxon and respective accession CAM metabolisms has been confirmed and maternal phylogenetic affinity with T. purpurea has been documented sequencing the rbcL gene (Hermida-Carrera et al 2020).…”
Section: Phylogenetic Reconstructions Are Congruent With Traditional Conceptsmentioning
confidence: 99%